PENYULUHAN PEMANFAATAN LIMBAH BUDIDAYA IKAN GABUS (channa striata) PADA BUDIDAYA CACING SUTRA (Tubifex SP.) SEBAGAI PAKAN ALAMI BIBIT IKAN PADA POKDAKAN MAJU BERSAMA MESUJI, DESA SUNGAI BADAK, KECAMATAN MESUJI KABUPATEN MESUJI - Ciptaning Weargo Jati; Huriyatul Fitriyah Noor; Septi Malidda Eka Putri (Jurnal Media Pengabdian Kepada Masyarakat, 2023)
The progress of the fish farming business, from hatchery to enlargement, is increasing from time to time. It can be seen from the increasing interest. The type of fish farming that is mostly carried out is the type of freshwater fish cultivation accompanied by technology that continues to develop. The role of natural feed as one of the determining factors for the success of fish hatchery businesses is often an obstacle because most cultivating communities still depend on natural products. Availability of natural food is important considering the mouth opening of fish larvae is small while the size of the feed that is not suitable is often a factor in the occurrence of premature death in the cultivation process. In addition, the amount of artificial feed that is not consumed by fish has the potential to damage the quality of the waters in the culture containers. Silk worms are an important natural feed in supporting fish hatcheries, freshwater fish are a determinant of the success of hatchery businesses both in terms of quality and quantity. Knowledge about silk worms is still very little known to the public. The result of this dedication is expected. The Pokdakan Maju Together with Mesuji, can utilize the waste of snakehead fish cultivation as a medium for the cultivation of silk worms (Tubifex sp.). Keywords: Freshwater Fish, Silk Worms, Natural Food